Case report: Severe non-pigmenting fixed drug eruption showing general symptoms caused by chondroitin sulfate sodium - Otsuka, Haruhiko; Fukumoto, Takeshi; Oka, Masahiro; Nishigori, Chikako (Frontiers in Medicine, 2022)
Non-pigmenting fixed drug eruption (NPFDE) is a subtype of fixed drug eruption (FDE), in which repeated eruptions occur at the same site. Clinically, NPFDE disappears without pigmentation changes but sometimes causes fever or arthralgia. Its histopathological characteristics reportedly include infiltrations of CD8-positive T-cells with a paucity of melanocytes compared with those in FDE. We present the first case of a severe NPFDE exhibiting general symptoms caused by chondroitin sulfate sodium. The patient was a 44-year-old man. Intravenous injection of chondroitin sulfate sodium caused erythema at the affected area. Histopathological examination of biopsy tissue revealed infiltration of CD3-positive lymphocytes into the epidermis (both CD4-positive lymphocytes and CD8-positive lymphocytes), minimal liquefaction degeneration in the basal layer of the epidermis, and few dermal melanophages. This factor may be responsible for non-pigmentation. This report documents a case of severe NPFDE showing general symptoms, caused by chondroitin sulfate sodium.